Aspek Molekuler Apoptosis: Peran Keluarga Bcl-2 dan Keluarga Caspase - Nurtami Nurtami; Elza Ibrahim Auerkari (Faculty of Dentistry, Universitas Indonesia, 2015)
Apoptosis, known as programmed cell death, is described as a form of cell death characterized by several morphological and biochemical features, such as membrane blebbing, cytoplasmic and nuclear condensation, DNA fragmentation and formation of apoptosis bodies. Genetic studies on Caeneorhabditis elegans have been further extended to apoptosis in mammals. Apoptosis is required for normal tissue homeostasis, which allows the organism to tightly control cell numbers and tissue size, and protect itself from rogue cells. The basic components that play a major role in apoptosis include the Bcl-2 and Caspase families. Bcl-2 family functions as either pro or anti-apoptosis, while the Caspase family includes the central executioner, the basic effectors of apoptosis, leading ultimately to fragmentation of DNA. This review describes the role of Bcl-2 and Caspase families in the process of apoptosis.